Influence of non-visual factors on visual preferences of visitors to small urban parks in Tabriz, Iran - Shahhosseini, Habib (2014)
The small urban parks (SUP) are the urban parks that vary in size from .04 to 2 hectares and are located close to the neighborhood areas in the cities. These parks play important roles in enhancing the urban life quality by providing easy access to green areas for recreation, leisure, and community interactions. Due to their important roles, increasing numbers of these parks are being built all over the world. The small urban parks provide intimate spaces where the users are more aware of the multidimensional sensory experiences. Unfortunately, most knowledge regarding the design of the parks in general is based on their visual dimensions. This study was an attempt to investigate both visual and non-visual preferences for the small urban parks. The visual factors investigated in this research included the Prospect, Refuge,Mystery, Legibility, Coherence, and Complexity, while the non-visual factors encompassed the sound, smell, and touch. The study was conducted in several selected SUPs in the city of Tabriz, Iran. A total of 394 visitors volunteered to participate in this survey in which photograph surrogate the actual scenes and textual questionnaires were used. A panel of experts advised the researcher in selecting a total of 52 scenes, representing the variables of the visual preferences in 6 categories. The questionnaire contained 76 items divided into three parts, were categorized as non-visual factors with the help of the nominal group technique (NGT) and based on the literature. The data was analysed using the descriptive and inferential statistics as well as the principle components analysis and the confirmatory factor analysis. Using the descriptive analysis, the public’s ranked order preferences were Natural,Spiritual, Human, Instrumental, and Mechanical (for sound), in addition Natural,Human-body, and Environmental related (for smell), and finally Natural and Furniture (for touch). The obtained results indicated that for the visual factors,Mystery had the highest value, whilst Prospect achieved the lowest public preference. The Structural Equation Modeling (SEM) revealed that the natural stimulus (Natural sound-smell) as well as human related stimulus (Human body sound-smell) exerted significant effects on the visual preferences, while the Instrumental sound, Touch factors and Environmental sound-smell stimulus did not receive any significant values. Meanwhile, the final structural model showed that the Kaplan-Kaplan information-processing theory could be reliable in defining the public’s visual preferences in relation to the non-visual factors. However, it is important to note that Legibility and Prospect from the Appleton theory and Coherence constructs were removed from the final structural model due to their high correlations with other variables. Probably, understanding in which order the non-visual factors influence the visual preferences would be a primary implication of this study. Hence, it could be concluded that consideration of the public multi-sensory experiences shape a robust way in the design approach which challenge the designers and policy makers to improve their attitudes towards designing the small urban parks. Application of the sound levels, sound sources, the amount of smell, attention to Natural and Human body stimulus, and consideration of other types of manmade touch toward the visual preferences would be suggested for future studies.